Circ_0000215 Exerts Oncogenic Function in Nasopharyngeal Carcinoma by Targeting miR-512-5p - Chen, Xinping; Xu, Weihua; Ma, Zhichao; Zhu, Juan; Hu, Junjie; Li, Xiaojuan; Fu, Shengmiao (Frontiers in Cell and Developmental Biology, 2021)
Background: Increasing circular RNAs (circRNAs) are reported to participate in cancer progression. Nonetheless, the role of circRNAs in nasopharyngeal carcinoma (NPC) has not been fully clarified. This work is aimed to probe the role of circ_0000215 in NPC. Methods: Circ_0000215 expression in NPC tissues and cell lines was examined by quantitative real-time polymerase chain reaction (qRT-PCR). Cell counting kit-8 (CCK-8) assay, 5-bromo-2'-deoxyuridine (BrdU) assay, scratch healing assay and Transwell experiment were executed to investigate the regulatory function of circ_0000215 on the proliferation, migration and invasion of NPC cells. RNA immunoprecipitation (RIP), pull-down and dual-luciferase reporter experiments were utilized to determine the binding relationship between circ_0000215 and miR-512-5p, and between miR-512-5p and phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) 3’UTR. The effects of circ_0000215 on NPC growth and metastasis in vivo were examined with nude mice model. Western blot was applied to detect the regulatory effects of circ_0000215 and miR-512-5p on PIK3R1 expression. Results: Circ_0000215 was overexpressed in NPC tissues and cell lines. The functional experiments confirmed that knockdown of circ_0000215 impeded the growth and metastasis of NPC cells in vitro and in vivo. Additionally, circ_0000215 could also work as a molecular sponge to repress miR-512-5p expression. PIK3R1 was validated as a target gene of miR-512-5p, and circ_0000215 could increase the expression level of PIK3R1 in NPC cells via suppressing miR-512-5p. Conclusion: Circ_0000215 is overexpressed in NPC and exerts oncogenic effects in NPC through regulating miR-512-5p/PIK3R1 axis.